Efficient Protocol for In vitro Regeneration of Ocimum sanctum using Nodal Segments as Explants: Regeneration of Ocimum sanctum (Biological Sciences - PJSIR, 2021)
Ocimum sanctum commonly called (holy basil) an herb containing medicinal, ornamental values, is often used in culinary applications. This research focuses on the improved and efficient protocol for the direct regeneration and acclimatisation of Ocimum sanctum using nodal segments. Organogenesis and multiplication from explants were observed to a maximum on Murashige and Skoog (MS) medium supplemented with 0.1 mg/L of 6-Benzyl amino purine (BAP) and 0.025 mg/L of Indole-3-acetic acid (IAA). Furthermore, same medium was found effective for the induction of roots, in the in-vitro grown plantlets. A series of experiments were conducted to optimise the acclimatisation of in-vitro grown rooted plantlets of Ocimum sanctum. For this study different types of potting mix in assorted ratios were used  to obtain best supporting media for the acclimatisation, A7 media containing soil : farmyard manure (75:25) and A1 media containing (100%) sand were found best supporting medium for the acclimatisation and hardening of Ocimum sanctum.